Incidence of Intra-Abdominal Hypertension and Abdominal Compartment Syndrome: A Systematic Review. (February 2021) - Khot, Zaid; Murphy, Patrick B.; Sela, Nathalie; Parry, Neil G.; Vogt, Kelly; Ball, Ian M.
Objective: To determine the contemporary prevalence of intra-abdominal hypertension (IAH) and abdominal compartment syndrome in critically ill patients. Data Sources: Medline, Embase, and Central databases. Study Selection: Studies reporting on the prevalence of IAH in consecutively admitted critically ill patients using the World Society of Abdominal Compartment Syndrome (WSACS) consensus guidelines for intra-abdominal pressure (IAP) measurement. Data Extraction: Duplicate independent review and data abstraction. Data Synthesis: The search identified 2428 titles with 6 eligible studies (n = 1965). Reported prevalence ranged from 30% to 49%. Despite abiding by the WSACS guidelines for IAP measurement, studies varied in their definition of IAH, frequency and duration of IAP measurement, and reporting of outcomes. Three of 6 studies reported that IAH, especially at higher grades, was an independent predictor of mortality. Conclusions: Intra-abdominal hypertension is a common finding in critically ill patients and may be associated with increased mortality, especially at higher grades. Further prospective research is required to examine the effect of screening and treatment of IAH on patient outcomes.